DNA methylation at the 9p21 glaucoma susceptibility locus is associated with normal-tension glaucoma. (4th March 2018) - Burdon, Kathryn P.; Awadalla, Mona S.; Mitchell, Paul; Wang, Jie Jin; White, Andrew; Keane, Miriam C.; Souzeau, Emmanuelle; Graham, Stuart L.; Goldberg, Ivan; Healey, Paul R.; Landers, John; Mills, Richard A. D.; et al.
ABSTRACT: Purpose: Recent genome-wide association studies reported strong association of genetic variation at the CDKN2B/CDKN2B-AS1 locus on 9p21 with normal-tension glaucoma (NTG) in multiple populations. The mechanism by which this locus causes disease remains to be elucidated. We investigated the association of DNA methylation of CpG islands at this locus with NTG. Methods: We conducted a retrospective case–control study of 178 NTG cases and 202 unaffected controls from Australia. CDKN2B and CDKN2B-AS1 promoter methylation was measured quantitatively using the MassCleave assay, and assessed for association with the disease, and the genotype of the associated risk variants using IBM SPSS statistics 22.0 CpG sites at which methylation status was associated with NTG were validated using pyrosequencing. Results: We identified one CpG site (F1:13–14) in the CDKN2B promoter which showed significant association with NTG ( p = 0.001). The association was highly significant in female cases ( p = 0.006) but not in male cases ( p = 0.054). The association was validated using an independent method confirming the likely association of DNA methylation with NTG in females ( p = 0.015), but not in males ( p = 0.497). In addition, methylation at CpG sites in CDKN2B was also associated with genotype at rs1063192, which is known to confer risk for NTG. Conclusion: This study reveals an association of methylation status in the CDKN2B promoter with NTG, particularly in females. This suggests that the observed genetic association with the disease at this locus could be in part due to epigenetic mechanisms, and is likely to be independent of the association of nonsynonymous coding variation within the gene.